Carbon tax and energy innovation at crossroads of carbon neutrality: Designing a sustainable decarbonization policy. (15th September 2021) - Cheng, Ya; Sinha, Avik; Ghosh, Vinit; Sengupta, Tuhin; Luo, Huawei
Abstract: Decarbonation has been a primary policy prerogative for Sweden, and carbon tax has been a primary policy instrument in this pursuit, and the revenue generated out of carbon tax has been a driver for energy innovation. However, the benefits of energy innovation have not been experienced across various sectors in Swedish economy, and it might be anticipated that the potential aim of achieving carbon neutrality might not be accomplished to the fullest. Hence, being faced with the need of policy realignment for Sweden, this study has made an attempt to discover the dynamics between carbon tax revenue and energy innovation over a period of 1990–2019, following Quantile-on-Quantile Regression framework. The results obtained from the study show that the impact of carbon tax revenue on energy innovation might turn out to be ineffective beyond a certain threshold limit. A similar pattern has also been observed for the impact of energy innovation on carbon tax revenue. This study gives an indication that there might be a non-linear association between both these model parameters. The study outcomes have paved a way to design a policy framework for helping Swedish economy to attain the objectives of Sustainable Development Goals, while paving the ways to achieve carbon neutrality. Highlights: Dynamics between carbon tax revenue and energy innovation is analyzed. Advanced quantile framework is used. Study is done for Sweden over 1990–2019. Tradeoff between carbon tax and energy innovation is found. Thresholds of the association are significant for drawing implications.